Contributions of Inter-Institutional Collaborative Work in Extension Processes for Social Transformation: The Ugrosanta Case - Vargas Venegas, Marta (2021)
This work is carried out by the School of Planning and Social Promotion, which is part of the Faculty of Social Sciences of the National University of Costa Rica (UNA). This academic unit was created in 1974; it has been characterized by integrating extension practices in teaching processes and promoting the active participation in students, academic teams, communities, and institutions through collaborative work that seeks the interaction between different social actors in favor of social transformation.This article presents the results of a 3-year collaborative work, developed in the community of Santa Cruz de Turrialba, Costa Rica, in coordination with the National System of Conservation Areas (SINAC), the organization Unión de Agrupaciones de Santa Cruz de Turrialba (UGROSANTA), fifteen students, and two teachers from the School of Planning and Social Promotion (EPPS) of the National University. In addition, the project had the participation of the Ministry of Culture and Youth of Costa Rica.First, key concepts for this analysis are highlighted, such as collaborative work, university extension, and rural development with a territorial approach as a basis for social transformation. Subsequently, the case study and the methodology used to write this article are contextualized. Finally, the results of the interviews conducted and the academic reflections generated by the development of the university-society relationship through collaborative work are presented.